A membrane treatment process for sewage
By using composite film materials in sewage treatment, combined with photocatalytic technology and membrane technology, the problem of existing sewage treatment technologies being difficult to achieve high efficiency, low cost and environmentally friendly, and the effective removal of organic pollutants and photocatalyst recovery are achieved. , improves processing efficiency and membrane life.
Patent Information
- Application Number
- CN202411492481.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-24
AI Technical Summary
Existing sewage treatment technologies are difficult to achieve high efficiency, low cost, convenient operation and management and environmentally friendly treatment effects at the same time, especially when coupling membrane technology with photocatalytic technology, it lacks effective research and application.
Using composite film materials, including matrix resin and ternary metal sulfide/MXene heterostructure composite materials, the wastewater is purified under light conditions, and a microsphere structure is formed through thiourea intercalation MXene and low-temperature freeze-drying to enhance photocatalytic activity. , and the effective recovery of photocatalysts is achieved through film technology.
Effectively remove organic pollutants and pathogenic microorganisms in water, improve photocatalytic efficiency, extend the service life of the membrane, and realize efficient separation and recovery of photocatalysts.
Smart Images

Figure CN118993237B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sewage treatment, in particular to a sewage membrane treatment process. Background Art
[0002] Traditional sewage treatment technologies such as chemical methods, physical methods, and ecological treatment technologies can no longer meet the requirements of high efficiency, low cost, convenient operation and management, and environmental friendliness. Finding efficient and low-consumption technologies to complete the treatment and disposal of complex water quality has attracted much attention. Among them, membrane technology is increasingly widely used in sewage treatment due to its advantages such as small footprint, simple operation and maintenance, and high treatment efficiency. However, there are relatively few studies on coupling membrane technology with photocatalytic technology for sewage treatment. Summary of the invention
[0003] Purpose of the invention: In view of the above technical problems, the present invention proposes a membrane treatment process for sewage.
[0004] The technical solutions adopted are as follows:
[0005] A membrane treatment process for sewage:
[0006] Under light conditions, the composite membrane material is used to purify sewage;
[0007] The composite film material comprises a matrix resin and a ternary metal sulfide / MXene heterostructure composite material.
[0008] Furthermore, the ternary metal sulfide / MXene heterostructure composite material has a microspherical structure.
[0009] Furthermore, the ternary metal sulfide is a cobalt-based ternary metal sulfide.
[0010] Furthermore, the ternary metal sulfide is MCo2S4, wherein M is any one of Cu, Zn, and Ni.
[0011] Furthermore, the preparation method of the ternary metal sulfide / MXene heterostructure composite material is as follows:
[0012] The M salt, cobalt salt, thiourea intercalated MXene and organic solvent are mixed, ultrasonically vibrated, and after the solvothermal reaction, the precipitate is collected, washed and dried.
[0013] Furthermore, the organic solvent is a combination of ethylene glycol and DMF, and the mass ratio of ethylene glycol to DMF is 1-5:1-5, preferably 1:1.
[0014] Furthermore, the preparation method of the thiourea intercalated MXene is as follows:
[0015] Add MXene to a mixed solvent of dimethyl sulfoxide and deionized water, and stir the reaction for 1-10 hours under water bath heating. After the reaction, collect the precipitate, wash and dry it to obtain dimethyl sulfoxide intercalated MXene, add it to methanol, stir the reaction for 1-10 days, and obtain methanol intercalated MXene. Finally, add methanol intercalated MXene to a saturated thiourea methanol solution, and react for 10-50 hours under water bath heating. After the reaction, collect the product, wash it and freeze-dry it at low temperature.
[0016] Furthermore, the temperature of low-temperature freeze drying is ≤-80°C, the vacuum degree is ≤10 Pa, and the time is ≥24h.
[0017] Furthermore, the solvent thermal reaction temperature is 160-200° C., and the solvent thermal reaction time is 12-72 h.
[0018] Furthermore, the matrix resin is any one or more combinations of polyvinyl alcohol resin, epoxy resin, polyester resin, bismaleimide resin, thermosetting polyimide resin, furan resin, polybutadiene resin, silicone resin, polytetrafluoroethylene resin, and polyvinylidene fluoride resin.
[0019] Furthermore, the mass ratio of the matrix resin to the ternary metal sulfide / MXene heterostructure composite material is 10-100:1.
[0020] Beneficial effects of the present invention:
[0021] The present invention provides a membrane treatment process for sewage. Photocatalysis technology, as a green cleaning technology, can effectively remove organic pollutants in water and inhibit pathogenic microorganisms in water. The layered structure and size effect of MXene are conducive to the construction of photocatalysts, which generate photogenerated electrons and holes under light. These electrons and holes have strong redox ability and can react with water and oxygen to generate free radicals. These free radicals have extremely strong oxidizing properties and can oxidize many organic pollutants, thereby achieving the degradation of pollutants.
[0022] The thiourea intercalated MXene in the present invention can not only introduce a sulfur source for the synthesis of the ternary metal sulfide, but also increase the interlayer distance of the MXene by intercalation and low-temperature freeze-drying. Under the action of hydrogen bonds between MXene layers and between MXene and thiourea molecules, the MXene self-assembles into a stable microspherical structure. Due to the unique morphology and structure and excellent charge transfer performance, the photocatalytic activity is improved. A strong interface interaction is established between the ternary metal sulfide and the MXene to form a heterojunction. The formation of the heterojunction promotes the effective separation of electron-hole pairs generated by light, improves the photocatalytic efficiency, overcomes the defects of the MXene narrow band gap, fast recombination of electrons and holes, and low utilization rate of visible light, and greatly improves its application range in photocatalytic degradation of organic pollutants. The present invention couples membrane technology with photocatalysis to construct a membrane material with composite functions, which can not only use photocatalysis to treat sewage, but also use the efficient separation of membrane technology to achieve effective recovery of photocatalysts. Moreover, the super-hydrophobic surface of the composite membrane material makes it difficult for organic pollution to adhere to the membrane surface, thereby extending the service life of the membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a SEM image of the NiCo2S4 / MXene heterostructure composite material prepared in Example 1;
[0024] Figure 2 This is a cross-sectional SEM image of the composite membrane material prepared in Example 1. DETAILED DESCRIPTION
[0025] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0026] Embodiment 1:
[0027] A membrane treatment process for sewage, which uses composite membrane materials to purify sewage under light conditions;
[0028] Wherein, the preparation method of the composite membrane material is as follows:
[0029] 10g MXene (Ti3C2T x) The multilayer nanosheets were added to a mixed solvent consisting of 120 ml of dimethyl sulfoxide and 12 ml of deionized water, and stirred for reaction at 90 °C in a water bath for 10 h. After the reaction, the precipitate was collected and washed thoroughly with anhydrous ethanol, and then dried in an oven at 60 °C for 24 h to obtain dimethyl sulfoxide intercalated MXene, which was added to 500 ml of methanol, stirred at room temperature for reaction for 7 days, and then filtered to obtain methanol intercalated MXene. Finally, the methanol intercalated MXene was added to 500 ml of saturated thiourea methanol solution, and reacted at 45 °C in a water bath for 48 h. After the reaction, the product was collected by suction, washed thoroughly with anhydrous ethanol, and then freeze-dried in a low-temperature freeze dryer at a temperature of -80 °C and a vacuum degree of 10 Pa for 72 h to obtain thiourea intercalated MXene;
[0030] 0.01 mol nickel nitrate hexahydrate, 0.02 mol cobalt acetate tetrahydrate, 1 g thiourea intercalated MXene, 50 ml ethylene glycol and 50 ml DMF were mixed, ultrasonically vibrated for 30 min, poured into a polytetrafluoroethylene-lined autoclave, sealed and heated to 180 °C for solvent thermal reaction for 48 h, filtered, and the precipitate was fully washed with deionized water and anhydrous ethanol and vacuum dried at 60 °C for 24 h to obtain a NiCo2S4 / MXene heterostructure composite material (the mass difference between the NiCo2S4 / MXene heterostructure composite material and the thiourea intercalated MXene was compared by weighing method to calculate the mass of the deposited NiCo2S4);
[0031] 20g PVDF was added to 150ml DMF and stirred to dissolve. Then 1g NiCo2S4 / MXene heterostructure composite material was added and mechanically stirred for 1h under ultrasonic oscillation to obtain a slurry. The slurry was vacuum degassed and poured onto a glass plate to form a film. The film was gently removed with a scraper and immersed in deionized water for 24h. The water was changed every 6h. After being taken out, it was placed in an oven at 80℃ for 10h. The oven was heated to 120℃ and kept for 30min before being taken out to obtain a composite membrane material with a thickness of 100±5μm. It was placed on a fully automatic contact angle measuring instrument and 2µL of deionized water was squeezed out of a syringe each time to stick to its surface. After 5s, the contact angle data was read out using the software Advance. Five points were evenly taken for measurement, and the final average value was 161°.
[0032] Embodiment 2:
[0033] The method is basically the same as Example 1, except that the preparation method of the composite membrane material is as follows:
[0034] 10g MXene (Ti3C2T x) The multilayer nanosheets were added to a mixed solvent consisting of 120 ml of dimethyl sulfoxide and 12 ml of deionized water, and stirred for reaction at 90 °C in a water bath for 10 h. After the reaction, the precipitate was collected and washed thoroughly with anhydrous ethanol, and then dried in an oven at 60 °C for 24 h to obtain dimethyl sulfoxide intercalated MXene, which was added to 500 ml of methanol, stirred at room temperature for reaction for 7 days, and then filtered to obtain methanol intercalated MXene. Finally, the methanol intercalated MXene was added to 500 ml of saturated thiourea methanol solution, and reacted at 45 °C in a water bath for 48 h. After the reaction, the product was collected by suction, washed thoroughly with anhydrous ethanol, and then freeze-dried in a low-temperature freeze dryer at a temperature of -80 °C and a vacuum degree of 10 Pa for 72 h to obtain thiourea intercalated MXene;
[0035] 0.01 mol nickel nitrate hexahydrate, 0.02 mol cobalt acetate tetrahydrate, 1 g thiourea intercalated MXene, 50 ml ethylene glycol and 50 ml DMF were mixed, ultrasonically vibrated for 30 min, poured into a polytetrafluoroethylene-lined autoclave, sealed and heated to 160 ° C for solvent thermal reaction for 72 h, filtered, and the precipitate was fully washed with deionized water and anhydrous ethanol and vacuum dried at 60 ° C for 24 h to obtain a NiCo2S4 / MXene heterostructure composite material;
[0036] 20g PVDF was added to 150ml DMF and stirred to dissolve. Then 1g NiCo2S4 / MXene heterostructure composite material was added and mechanically stirred for 1h under ultrasonic oscillation to obtain a slurry. The slurry was vacuum degassed and poured onto a glass plate to form a film. The film was gently removed with a scraper and immersed in deionized water for 24h. The water was changed every 6h. After being taken out, it was placed in an oven at 80℃ for 10h. The oven was heated to 120℃ and kept for 30min before being taken out to obtain a composite membrane material with a thickness of 100±5μm. It was placed on a fully automatic contact angle measuring instrument and 2µL of deionized water was squeezed out of a syringe each time to stick to its surface. After 5s, the contact angle data was read out using the software Advance. Five points were evenly taken for measurement, and the final average value was 149°.
[0037] Embodiment 3:
[0038] The method is basically the same as Example 1, except that the preparation method of the composite membrane material is as follows:
[0039] 10g MXene (Ti3C2T x) The multilayer nanosheets were added to a mixed solvent consisting of 120 ml of dimethyl sulfoxide and 12 ml of deionized water, and stirred for reaction at 90 °C in a water bath for 10 h. After the reaction, the precipitate was collected and washed thoroughly with anhydrous ethanol, and then dried in an oven at 60 °C for 24 h to obtain dimethyl sulfoxide intercalated MXene, which was added to 500 ml of methanol, stirred at room temperature for reaction for 7 days, and then filtered to obtain methanol intercalated MXene. Finally, the methanol intercalated MXene was added to 500 ml of saturated thiourea methanol solution, and reacted at 45 °C in a water bath for 48 h. After the reaction, the product was collected by suction, washed thoroughly with anhydrous ethanol, and then freeze-dried in a low-temperature freeze dryer at a temperature of -80 °C and a vacuum degree of 10 Pa for 72 h to obtain thiourea intercalated MXene;
[0040] 0.01 mol nickel nitrate hexahydrate, 0.02 mol cobalt acetate tetrahydrate, 1 g thiourea intercalated MXene, 50 ml ethylene glycol and 50 ml DMF were mixed, ultrasonically vibrated for 30 min, poured into a polytetrafluoroethylene-lined autoclave, sealed and heated to 200 °C for solvent thermal reaction for 12 h, filtered, and the precipitate was fully washed with deionized water and anhydrous ethanol and vacuum dried at 60 °C for 24 h to obtain a NiCo2S4 / MXene heterostructure composite material;
[0041] 20g PVDF was added to 150ml DMF and stirred to dissolve. Then 1g NiCo2S4 / MXene heterostructure composite material was added and mechanically stirred for 1h under ultrasonic oscillation to obtain a slurry. The slurry was vacuum degassed and poured onto a glass plate to form a film. The film was gently removed with a scraper and immersed in deionized water for 24h. The water was changed every 6h. After being taken out, it was placed in an oven at 80℃ for 10h. The oven was heated to 120℃ and kept for 30min before being taken out to obtain a composite membrane material with a thickness of 100±5μm. It was placed on a fully automatic contact angle measuring instrument and 2µL of deionized water was squeezed out of a syringe each time to stick to its surface. After 5s, the contact angle data was read out using the software Advance. Five points were evenly taken for measurement, and the final average value was 152°.
[0042] Comparative Example 1:
[0043] The same as Example 1, except that MXene (Ti3C2T x ) Multilayer nanosheets instead of NiCo2S4 / MXene heterostructure composites;
[0044] The preparation method of the composite membrane material is as follows:
[0045] 20 g of PVDF was added to 150 ml of DMF and stirred to dissolve. Then 1 g of MXene (Ti3C2T x) multilayer nanosheets were added and mechanically stirred for 1 hour under ultrasonic oscillation to obtain a slurry. The slurry was vacuum degassed and poured onto a glass plate to form a film. The film was gently removed with a scraper and immersed in deionized water for 24 hours. The water was changed every 6 hours. After being taken out, it was placed in an oven at 80°C for 10 hours. The oven was then heated to 120°C and kept for 30 minutes before being taken out to obtain a composite membrane material with a thickness of 100±5μm. It was placed on a fully automatic contact angle measuring instrument and 2µL of deionized water was squeezed out of a syringe each time to stick to its surface. After 5s, the contact angle data was read out using the software Advance. Five points were evenly taken for measurement, and the final average value was 136°.
[0046] Comparative Example 2:
[0047] The same as Example 1, except that thiourea intercalated MXene was used instead of NiCo2S4 / MXene heterostructure composite material;
[0048] The preparation method of the composite membrane material is as follows:
[0049] 10g MXene (Ti3C2T x ) The multilayer nanosheets were added to a mixed solvent consisting of 120 ml of dimethyl sulfoxide and 12 ml of deionized water, and stirred for reaction at 90 °C in a water bath for 10 h. After the reaction, the precipitate was collected and washed thoroughly with anhydrous ethanol, and then dried in an oven at 60 °C for 24 h to obtain dimethyl sulfoxide intercalated MXene, which was added to 500 ml of methanol, stirred at room temperature for reaction for 7 days, and then filtered to obtain methanol intercalated MXene. Finally, the methanol intercalated MXene was added to 500 ml of saturated thiourea methanol solution, and reacted at 45 °C in a water bath for 48 h. After the reaction, the product was collected by suction, washed thoroughly with anhydrous ethanol, and then freeze-dried in a low-temperature freeze dryer at a temperature of -80 °C and a vacuum degree of 10 Pa for 72 h to obtain thiourea intercalated MXene;
[0050] 20g PVDF was added to 150ml DMF and stirred to dissolve. Then 1g thiourea intercalated MXene was added and mechanically stirred for 1h under ultrasonic oscillation to obtain a slurry. The slurry was vacuum degassed and poured onto a glass plate to form a film. The film was gently removed with a scraper and immersed in deionized water for 24h. The water was changed every 6h. After being taken out, it was placed in an oven at 80℃ for 10h. The oven was heated to 120℃ and kept for 30min before being taken out to obtain a composite membrane material with a thickness of 100±5μm. It was placed on a fully automatic contact angle measuring instrument and 2µL of deionized water was squeezed out of a syringe each time to stick to its surface. After 5s, the contact angle data was read out using the software Advance. Five points were evenly taken for measurement, and the final average value was 148°.
[0051] Comparative Example 3:
[0052] The method is basically the same as Example 1, except that thiourea intercalated MXene and NiCo2S4 are added separately (the mass ratio of thiourea intercalated MXene and NiCo2S4 is the same as that of Example 1);
[0053] The preparation method of the composite membrane material is as follows:
[0054] 10g MXene (Ti3C2T x ) The multilayer nanosheets were added to a mixed solvent consisting of 120 ml of dimethyl sulfoxide and 12 ml of deionized water, and stirred for reaction at 90 °C in a water bath for 10 h. After the reaction, the precipitate was collected and washed thoroughly with anhydrous ethanol, and then dried in an oven at 60 °C for 24 h to obtain dimethyl sulfoxide intercalated MXene, which was added to 500 ml of methanol, stirred at room temperature for reaction for 7 days, and then filtered to obtain methanol intercalated MXene. Finally, the methanol intercalated MXene was added to 500 ml of saturated thiourea methanol solution, and reacted at 45 °C in a water bath for 48 h. After the reaction, the product was collected by suction, washed thoroughly with anhydrous ethanol, and then freeze-dried in a low-temperature freeze dryer at a temperature of -80 °C and a vacuum degree of 10 Pa for 72 h to obtain thiourea intercalated MXene;
[0055] 20g PVDF was added to 150ml DMF and stirred to dissolve it. Then 1g of thiourea intercalated MXene and NiCo2S4 were added and mechanically stirred for 1h under ultrasonic oscillation to obtain a slurry. The slurry was vacuum degassed and poured onto a glass plate to form a film. The film was gently removed with a scraper and immersed in deionized water for 24h. The water was changed every 6h during this period. After being taken out, it was placed in an oven at 80℃ for 10h. The oven was heated to 120℃ and kept for 30min before being taken out to obtain a composite membrane material with a thickness of 100±5μm. It was placed on a fully automatic contact angle measuring instrument and 2µL of deionized water was squeezed out of a syringe each time to stick to its surface. After 5s, the contact angle data was read out using the software Advance. Five points were evenly taken for measurement, and the final average value was 157°.
[0056] Performance testing:
[0057] 1 g of the composite film material prepared in Examples 1-3 and Comparative Examples 1-3 was taken as a sample to test the photocatalytic degradation performance;
[0058] Specific process: Use 60mg / L rhodamine (RhB) solution as simulated wastewater, add 50ml RhB solution into a 100ml culture dish, make sure the sample is immersed in the solution and left in the dark for 30min to reach adsorption-desorption equilibrium, then turn on the ultraviolet lamp (500W) for 30min. After the photocatalysis is completed, extract 1ml RhB solution from the suspension and detect its absorbance at a wavelength of 554nm.
[0059] In addition, a 60 mg / L methylene blue (MB) solution was used as simulated wastewater, and the photocatalytic degradation performance was tested using the same method. After the photocatalysis was completed, 1 ml of MB solution was extracted from the suspension and its absorbance was detected at a wavelength of 664 nm.
[0060] The photocatalytic degradation efficiency was calculated using the following formula:
[0061] ;
[0062] Where η is the photocatalytic degradation efficiency, A0 and A1 are the absorbances of RhB or MB before and after degradation, respectively.
[0063] The test results are shown in Table 1 below:
[0064] Table 1:
[0065] ;
[0066] It can be seen from Table 1 above that the composite film material prepared by the present invention has a good photocatalytic effect on organic pollutants.
[0067] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A membrane treatment process for sewage, characterized in that: Under light conditions, the composite membrane material is used to purify sewage; The composite film material comprises a matrix resin and a ternary metal sulfide / MXene heterostructure composite material; The ternary metal sulfide / MXene heterostructure composite material has a microspherical structure; The ternary metal sulfide is MCo2S4, wherein M is any one of Cu, Zn and Ni; The preparation method of the ternary metal sulfide / MXene heterostructure composite material is as follows: Mix M salt, cobalt salt, thiourea intercalated MXene and organic solvent, perform ultrasonic oscillation, and after solvothermal reaction, collect the precipitate, wash it and dry it; Wherein, the preparation method of the thiourea intercalated MXene is as follows: Add MXene to a mixed solvent of dimethyl sulfoxide and deionized water, and stir the reaction for 1-10 hours under water bath heating. After the reaction, collect the precipitate, wash and dry it to obtain dimethyl sulfoxide intercalated MXene, add it to methanol, stir the reaction for 1-10 days, and obtain methanol intercalated MXene. Finally, add methanol intercalated MXene to a saturated thiourea methanol solution, and react for 10-50 hours under water bath heating. After the reaction, collect the product, wash it and freeze-dry it at low temperature.
2. The membrane treatment process for sewage according to claim 1, characterized in that: The temperature of low-temperature freeze drying is ≤-80℃, the vacuum degree is ≤10 Pa, and the time is ≥24h.
3. The membrane treatment process for sewage according to claim 1, characterized in that: The solvent thermal reaction temperature is 160-200°C, and the solvent thermal reaction time is 12-72h.
4. The membrane treatment process for sewage according to claim 1, characterized in that: The matrix resin is any one or more combinations of polyvinyl alcohol resin, epoxy resin, polyester resin, bismaleimide resin, thermosetting polyimide resin, furan resin, polybutadiene resin, silicone resin, polytetrafluoroethylene resin, and polyvinylidene fluoride resin.
5. The membrane treatment process for sewage according to claim 1, characterized in that: The mass ratio of the matrix resin to the ternary metal sulfide / MXene heterostructure composite material is 10-100:1.